Technical services management 1965 - 1990 : - Smith, Linda C. (Haworth Press, 1996)
Each chapter is valuable in its own right, but the entire collection is much more valuable than the sum of its parts... The editor have made an excellent choice of topics, giving appropriate emphasis to such traditional subjects as acquisitions and descriptive cataloging, but also including activities such as preservation and indexing...